Inversion Formula for a Radon-Type Transform Arising in Photoacoustic Tomography with Circular Integrating Detectors - Sunghwan Moon (Advances in Mathematical Physics)
This paper is devoted to a Radon-type transform arising in a version of Photoacoustic Tomography that uses integrating circular detectors. The Radon-type transform that arises can be decomposed into the known Radon-type transforms: the spherical Radon transform and the sectional Radon transform. An inversion formula is obtained by combining existing inversion formulas for the above two Radon-type transforms.